Effectiveness of a Food Education Program for healthcare workers: a pilot study in a Total Worker Health© approach - Di Prinzio, Reparata Rosa; Dosi, Alessia; Arnesano, Gabriele; Vacca, Maria Eugenia; Melcore, Giuseppe; Maimone, Mariarita; Vinci, Maria Rosaria; Camisa, Vincenzo; Santoro, Annapaola; De Falco, Federica; De Maio, Federica; Dalmasso, Guendalina; et al. (Frontiers in Public Health, 2025)
IntroductionObesity has been identified as a crucial cause of non-communicable diseases, especially for healthcare workers who often take a brief lunch break with high energy and micro- and macronutrients deficient food.MethodsOur study aims to investigate the clinical and economic effectiveness of the “Food Education Program” (FEP) among healthcare workers having weight problems. Four questionnaires were administered before and after FEP to explore the risk of psychological injury (“Psychological Injury Risk Indicator”), mental and general health status (“Goldberg's General Health Questionnaire-12” and “Short Form-36 health survey”) and eating behavior (“Eating Attitudes Test”). The Return on Investment (ROI) was calculated on the base of absenteeism reduction in the 1-year period after FEP.ResultsFifty-one participants (78.4% females, mean age: 52.04 ± 8.94) were included in the study. They were mainly nurses (56.9%). 54.9% were obese and 43.1% overweight. The success rate was 32.1%; the reduction in BMI was more evident in the overweight participants than the obese subjects. A significant reduction of waist-to-hip ratio, glycosylated hemoglobin, total and LDL cholesterol, and an increase in vitamin D was observed (p-value: 0.047, 0.002, <0.001, 0.001, and 0.03). Scores on general health significantly improved (p-value <0.001 and 0.011). A mean per capita reduction of 3.70 days was observed in 1-year period after the intervention, with a ROI of 6.97.ConclusionFood Education Program represents a successful program to improve psychophysical wellbeing of healthcare workers through healthy nutritional plans, also having a notable positive impact on the organization, including its financial accounts.